2020
DOI: 10.5213/inj.1938116.058
|View full text |Cite
|
Sign up to set email alerts
|

Daily Pad Usage Versus the International Consultation on Incontinence Questionnaire Short Form for Continence Assessment Following Radical Prostatectomy

Abstract: Purpose: Continence assessment is an essential component of follow-up after radical prostatectomy (RP). Several methods exist to assess the severity of urinary incontinence (UI). Our study examined the relationship and degree of agreement between International Consultation on Incontinence Questionnaire Short Form (ICIQ-SF) scores and the number of pads used in a 24-hour period in the assessment of UI following RP.Methods: Continence was prospectively assessed in 746 men from a Spanish urology clinic 12 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
2
16
1
2
Order By: Relevance
“…It has good internal consistency and strong correlation with pad usage, aspects also demonstrated in our study (Cronbach's α = 0.815; and Spearman's ρ > 0.65 between the different items of ICIQ‐SF and pad usage) 10 . Some studies have observed a good or excellent concordance between ICIQ‐SF and pad usage 21 . This degree of concordance is not found in our study and is only acceptable when using the definition of 0 pads (Cohen's κ = 0.466) and is made worse by adopting less strict definitions 22 …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It has good internal consistency and strong correlation with pad usage, aspects also demonstrated in our study (Cronbach's α = 0.815; and Spearman's ρ > 0.65 between the different items of ICIQ‐SF and pad usage) 10 . Some studies have observed a good or excellent concordance between ICIQ‐SF and pad usage 21 . This degree of concordance is not found in our study and is only acceptable when using the definition of 0 pads (Cohen's κ = 0.466) and is made worse by adopting less strict definitions 22 …”
Section: Discussionsupporting
confidence: 80%
“…10 Some studies have observed a good or excellent concordance between ICIQ-SF and pad usage. 21 This degree of concordance is not found in our study and is only acceptable when using the definition of 0 pads (Cohen's κ = 0.466) and is made worse by adopting less strict definitions. 22 When assessing the deficit in QoL secondary to urinary leakage, we were unable to identify significant differences between patients with an ICIQ score = 0 and patients with an ICIQ score = 2, that is, there is no evidence that patients who never leak urine have a higher QoL than patients who leak "a small amount" of urine "about once a week."…”
Section: Discussioncontrasting
confidence: 68%
“…A broadly accepted conservative definition of urinary continence after radical prostatectomy has been pad-free status (no pad use per 24 h in the past week) 91 , 203 . Alternative definitions of continence include ‘social continence’ where pad use is ≤1 pad per day 91 , 108 .…”
Section: Application Of Transperineal Ultrasonographymentioning
confidence: 99%
“…The evaluation of urinary function directly by clinicians is often inadequate 204 , requiring the use of validated questionnaires to obtain patient-reported outcome measures 205 . Validated questionnaires, such as the International Consultation on Incontinence Questionnaire (ICIQ) on Male Lower Urinary Tract Symptoms (ICIQ‐MLUTS) 206 , 207 , a short form thereof (ICIQ-SF) 49 , 203 , 208 , the Expanded Prostate Cancer Index Composite (EPIC) 205 , 209 urinary incontinence domain and the University of California Los Angeles Prostate Cancer Index (UCLA-PCI), have been used 210 .…”
Section: Application Of Transperineal Ultrasonographymentioning
confidence: 99%
“…Some researchers believe that the criterion for full continence control is the lack of pads for 24 h in the last week. Other researchers believe that ≤1 pad per day means “social continence” [ 19 , 20 , 21 ]. Regardless of the adopted criteria, researchers report that UI may affect up to 80% of patients after RP [ 22 ].…”
Section: Introductionmentioning
confidence: 99%